Development of wafers with lowered glycemic index - N. N. Popova (Vestnik Voronežskogo Gosudarstvennogo Universiteta Inženernyh Tehnologij, 2017)
The negative impact on an organism is made by lack of culture of food of the population and low physical activity. It leads to violations of carbohydrate and lipidic exchange, development of obesity, diabetes, cardiovascular and other diseases. Relevance of development of foodstuff, in particular – the confectionery promoting decrease in risk of developing of such pathologies is proved. A research objective – development of a compounding of wafers with the lowered glycemic index. As an object of a research the wafers baked in house conditions are chosen. In work various characteristics are analysed (hygroscopicity, a cariogenicity sweet degree, power value, a glicemic index and a glycemic response) the sweetening substances, the choice of fructose as sugar substitute for production of wafers with the lowered glycemic index is reasonable. By optimization of a compounding of wafers the amount of sugar was replaced with amount of sweetener, equivalent on sweet. As a result of predesigns the interval of a variation of amount of the fructose entered into a compounding of wafers is established. Further assessment of the indicators of quality forming consumer demand of products – appearance, taste, a smell, existence of a crunch is carried out. Humidity of the received wafers after their production and in the course of storage is also investigated. Decrease in a glycemic index was fixed by amount of glucose in blood. Its measurements saw by means of the glucose meter "on an empty stomach" and after the use of wafers to a complete recovery of level of sugar in blood. The confectionery made on the optimized compounding practically doesn't differ on caloric content from a control sample, and glucose level in blood after their use on about 20% below.